Synopsis: The enabling environment for informal food traders in Nigeria’s secondary cities - Resnick, Danielle; Sivasubramanian, Bhavna; Idiong, Idiong Christopher; Ojo, Michael Akindele; Tanko, Likita (International Food Policy Research Institute, 2018)
Informal vendors are a critical source of food security in African cities and play a key role in food system transformation. However, the livelihoods of these traders and the governance constraints they encounter are not well-understood outside of primate cities. This study focuses on two distinct secondary cities in Nigeria – Calabar in the South-South geopolitical zone and Minna in the Middle Belt region. Local and state officials in each city were interviewed on the legal, institutional, and oversight functions they provide within the informal food sector. This was complemented with a survey of 1,097 traders across the two cities.